Pengaruh Ketimpangan Pendapatan, Indeks Pembangunan Manusia, dan Tingkat Pengangguran Terbuka Terhadap Tingkat Kemiskinan pada 10 Provinsi di Indonesia Ditinjau dalam Perspektif Ekonomi Islam Tahun 2015-2024 - Novita Sari; Madnasir Madnasir; Yulistia Devi; Ghina Ulfah Saefurrohman (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
In ten Indonesian provinces with the highest rates of poverty between 2015 and 2024, this study looked at the impact of open unemployment, income inequality, and the Human Development Index (HDI) on poverty. As part of a quantitative technique, this analysis makes use of panel data from Central Statistics Agency publications. After all collected data was analyzed using the panel data regression approach, tests conducted using the Eviews 12 application revealed that the Fixed Effect Model (FEM) was the best specification. The results show that income inequality has a major impact on rising rates of poverty. However, the HDI variable's positive but insignificant correlation shows that improvements in human development quality have not directly impacted the decline in poverty in these areas. In addition, the open unemployment rate was also not proven to affect changes in poverty levels. In the context of Islamic economics, equitable distribution of wealth, protection for vulnerable groups, and optimization of social instruments such as zakat, infaq, and sadaqah are crucial principles in maintaining economic justice.